Contributions to the taxonomy of Trachelyopterus (Siluriformes): comparative cytogenetic analysis in three species of Auchenipteridae - Santos,Dayane Petik dos (2021)
ABSTRACT Auchenipteridae is divided into subfamilies Centromochlinae and Auchenipterinae. Parauchenipterus is included in the latter and is subject of taxonomic discussions concerning its validation or synonymization with Trachelyopterus. Herein, three species from two hydrographic basins were cytogenetically analyzed: Parauchenipterus striatulus from Doce River and two sympatric species, P. galeatus and Trachelyopterus coriaceus, from the Araguaia River. Diploid number of 58 chromosomes was verified for all species, but P. striatulus has different karyotype formula from the others. The three species have heterochromatin located in terminal regions of almost all chromosomes and in pericentromeric region on acrocentric chromosomes. Simple NORs was verified on a subtelocentric chromosome for all species. 5S rDNA sites were detected in three submetacentric chromosome pairs in P. striatulus; in a metacentric chromosome pair and submetacentric pair in T. coriaceus; and in one metacentric chromosome pair in P. galeatus. The similarities found in the karyotypes of the three species suggest the existence of only one genus, Trachelyopterus; therefore, our data refutes the validation of Parauchenipterus. Moreover, the differences in 5S rDNA distribution in P. galeatus in comparison with other populations already studied, indicate the existence of a new taxonomic unit, which suggests a species complex in P. galeatus.